Effect of Tracheostomy Patient Care Training on the Performance of Nurses in Intensive Care Units - Zahra Kashaninia; Tahereh Najafi; Hamid Haghani; Sara Faramarzian (Iran University of Medical Sciences, 2023)
Background & Aims Tracheostomy is often performed for people hospitalized in intensive care units (ICUs), but it can cause larynx damage and discomfort in the patient. Given that the final outcome and possible complications of tracheostomy are directly related to the quality of nursing care, this study aims to evaluate the effect of tracheostomy care training on the performance of nurses working in the ICUs of selected hospitals affiliated to Iran University of Medical Sciences. Materials & Methods This quasi-experimental study was conducted on 64 nurses working in the ICUs of Rasul Akram and Firouzgar hospitals in 2021. The data collection tools were a demographic form and the tracheostomy patient care evaluation questionnaire of Atashzadeh et al. (2015). data analysis was performed in SPSS software, version 16 using descriptive and inferential statistics (paired t-test, and analysis of variance). P<0.05 was considered statistically significant. Results The mean age of nurses was 31.49±6.02 years. Most of them were female (70.3%) with a bachelor's degree (90.6%). Their mean overall work experience was 6.74±5.13 years, and their average work experience in the ICU was 4.92±4.66 years. Most of the nurses (43.8%) had permanent employment. Most of the nurses had rotating shift (89.1%), and had not completed the course of tracheostomy care (93.8%). The results of the paired t-test showed a statistically significant difference in the mean performance score of nurses before training (45.85±8.87) and after training (93.3±42.33) (P<0.001). Conclusion Considering that the performance of nurses in caring for patients with tracheostomy in the ICUs of selected hospitals is not satisfactory, educating nurses and providing sufficient facilities based on guidelines and opinions of experts are recommended to improve the quality of services to these patients by nurses in the hospitals.